Effect of Argument Driven Inquiry (ADI)-STEM Model on Students' Numeracy Literacy and Scientific Argumentation Skills - Laia, Syukurman; Siregar, Nurdin; Simanjuntak, Mariati Purnama (Postgraduate, University of Mataram, 2025)
This study aims to determine the significant effect of the argument driven inquiry (ADI)-STEM learning model on numeracy literacy and scientific argumentation skills of students on the subject matter of dynamic fluid class XI semester II at SMAN 10 Medan T.P 2024/2025. This type of research is a quasi experiment and the research design is a two-group pretest-posttest. The population in this research is the entire class XI of SMAN 10 Medan T.P 2024/2025. The sample in this study consisted of two classes selected randomly with simple random sampling technique, class XI IPA-1 as an experimental class using argument driven inqiry (ADI)-STEM learning model with a total of 36 students and class XI IPA-2 as a control class with conventional learning model with a total of 31 students. The instrument in this study was a test in the form of a 10 question essay. Data analysis was used with manova test. The results of the study were obtained with the average value of the numeracy literacy pretest of the experimental class and control class 53.89 and 54.19 respectively while the scientific argumentation of the experimental class and control class 52.22 and 51.68 respectively. The average post-test scores of numeracy literacy of experimental and control classes were 83.22 and 71.48 respectively while scientific argumentation of experimental and control classes were 86.78 and 70.90 respectively. Data analysis using manova test concluded that there is a significant effect of argument driven inquiry learning model on numeracy literacy and scientific argumentation